Strategi Menterjemah dan Upaya Pengentasan Probelamatika Penerjemahan Arab di Kalangan Mahasiswa - Meliza Budiarti (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2019)
If someone wants to get a good quality translation, a translator cannot add or reduce the meaning contained in the source language because it is affected by the original form of the target language. Translation is a bridge between the writer of source language text and the target language reader to make the text come naturally appropriate in the target language. This is certainly different when the results of a translation are still too related to the language and culture of the source. The translation will be wrong and rigid. A translator must master the translation strategy, namely: collocation, domestication and technicality. As well as aspects that must be understood, namely: accuracy, readability and acceptability. This can also be a reference for students in finding solutions to problems in translating difficulties, especially for the Arabic Language and Literature students.